Parasite or mutualist: the functional role of intracellular symbionts in shaping communities of agriculturally beneficial spiders - Gibbons, Alastair Tristan Russell (2020)
By the year 2050 the world's population is expected to grow to almost 10 billion. In order to meet future food demands a transformative change, at the global scale, in agricultural and food systems is required. Yet, the current trend for the overall growth of yields has slowed. Productivity has been hampered by the degradation of natural resources as well as the spread of pests and disease, including those that are developing resistance to agro-chemicals. In addition, the biodiversity decline, fuelled by intensive monocultures, uniform habitats and the excessive use of agro-chemicals is one of the greatest challenges society faces, and what is concurrent in the literature, is that these practices are becoming increasingly unsustainable.